Impact of environmental stimuli on consumers' price-quality-value perceptions : a study on Borders - Ang, Ai Peng (2008)
This research paper examines the relationship of environmental stimuli and consumers' price-quality-value perceptions of Borders Singapore. It covers the following areas: environmental stimuli attributes that are important to Singapore consumers, the relative importance of various stimuli to undergraduates and the perception of undergraduates on Borders Singapore.